Zonation by ammonites and foraminifers of the Vraconnian-Turonian interval: A comparison of the Boreal and Tethyan domains (NW Europe / Central Tunisia) - Amédro, Francis; Robaszynski, Francis (Carnets de géologie (Notebooks on geology), 2008)
Depuis la fin du 19ème siècle, l'intervalle comprenant l'Albien supérieur élevé, le Cénomanien, le Turonien et le Coniacien basal a été subdivisé d'abord en zones d'ammonites puis, à partir du milieu du 20ème siècle, en zones de foraminifères planctoniques, deux groupes de macro- et de microfossiles particulièrement efficaces en bio-chronostratigraphie grâce à leur taux d'évolution rapide. Toutefois, des différences de compositions fauniques entre le domaine boréal (Europe du Nord-Ouest) et le domaine téthysien (Méditerranée) ont longtemps empêché des corrélations précises entre ces deux domaines. Aujour-d'hui, dans un intervalle de temps couvrant environ 16 millions d'années, on dénombre 29 zones d'am-monites en domaine téthysien contre 24 en domaine boréal parmi lesquelles 16 sont communes aux deux domaines. Pour les foraminifères planctoniques, on compte 11 zones en domaine téthysien et 10 en domaine boréal, dont 7 communes. Since the end of the 19th century the interval comprising the uppermost Upper Albian, the Cenomamian, the Turonian and the basal Coniacian has been subdivided, first into ammonite zones, then, beginning in the middle of the 20th century, into zones of planktonic foraminifera. These two groups, one macrofossil, the other microfossil, are particularly effective for bio-chronostratigraphy thanks to their rapid rates of evolution. But differences in the faunal makeup between the Boreal domain (northwestern Europe) and the Tethyan domain (Mediterranean) have for a long time hindered precise correlation of the two domains. Today, in a time interval covering about 16 million years, there are 29 ammonite zones in the Tethyan domain versus 24 in the Boreal one, of which 16 are common to both domains. For the planktonic foraminifera the Tethyan domain has 11 zones, the Boreal domain 10, with 7 in common.